Development of corrosion layer of steel bar in concrete and its mechanical and electrochemical effects. (8th February 2010) - Yuan, Yingshu; Ji, Yongsheng
Steel bar in concrete can be corroded under environment of chloride attack. The rust which has a characteristic of expansion and the porosity of the steel-concrete interface offer a space for diffusing of the expansive rust. The diffusion of the rust transforms the porous steel-concrete interface into the dense mixed layer composed of concrete and rust, the layer is called corrosion layer in this paper. The development of the corrosion layer leads to mechanical effect on corrosion cracking and electrochemical effect on retardation of oxygen and water transportation. The dense corrosion layer resists rust diffusion and produces an expansive force which finally forms corrosion cracking. The dense corrosion layer retards transporting oxygen and water to the surface of the steel bar and then the corrosion rate slows down. This paper describes the composition and distribution of the corrosion layer along the bar surface, presents the distribution model of expansive force and reveals time depended process of the variation of corrosion rate of the steel bar in concrete and discusses the mechanism of mechanical and electrochemical effects.